The Effects of Physical Activity and Structured Exercise on Metabolic Health and Cardiovascular Risk: A Comprehensive Review - Kowalczuk, Maciej; Michał Piskor; Pazio, Klaudia; Strzalińska, Dominika; Bajko, Julia; Kapusta , Kinga; Ciszewski, Artur; Chmielewski , Michał; Błażewicz, Juliusz; Zadykowicz, Jakub (Quality in Sport, 2026)
Background: Cardiovascular diseases (CVDs) remain the leading global cause of mortality and are increasingly recognised as a systemic metabolic–inflammatory disorder. Physical inactivity is a major modifiable risk factor, while regular physical activity is associated with broad cardiometabolic benefits. Methods: This narrative review synthesises evidence from meta-analyses, randomised controlled trials, and mechanistic studies identified through PubMed, Scopus, Web of Science, and JACC. Studies evaluating aerobic, resistance, combined, and high-intensity interval training (HIIT) were included. Outcomes included cardiovascular risk factors, inflammation, metabolic health, cardiorespiratory fitness, and clinical endpoints. Results: Regular physical activity reduces systemic inflammation (CRP, IL-6, TNF-α), improves endothelial function, and enhances insulin sensitivity. Combined aerobic and resistance training provides superior improvements in glycaemic control, including HbA1c reductions (~0.5%), fasting glucose, and lipid profiles compared with single-modality exercise. Clinically relevant reductions in blood pressure are observed, particularly in hypertensive populations (systolic ~5–10 mmHg). Exercise improves lipid profiles (↑HDL, ↓LDL and triglycerides) and reduces visceral fat (~7–20%). Improvements in VO₂ peak are strongly associated with reduced cardiovascular morbidity and mortality. A dose–response relationship is evident, with optimal benefits at 150–300 min/week of moderate-intensity activity. Sedentary behaviour independently increases cardiovascular risk. Despite benefits, adherence remains suboptimal, although digital tools and personalised interventions improve compliance. Conclusion: Physical activity is a cornerstone of cardiovascular disease prevention and management, improving metabolic, inflammatory, and haemodynamic health. Individualised and technology-supported exercise strategies may enhance long-term adherence and maximise clinical benefit.